Analysis of Pre-Test and Post-Test Results of Motor Skills through the Implementation of Small Games in Physical Education, Sports, and Health (PESH) Learning in Elementary Schools - sidiq, fahmi; Pirdaus, Dede Irman; Ismail, Muhammad Iqbal Al-Banna (International Journal of Ethno-Sciences and Education Research, 2024)
This research aims to evaluate the impact of implementing small games in Physical Education, Sports, and Health (PESH) learning on the improvement of motor skills among elementary school students. The research method employed is a pure experiment with a quantitative approach. Data was collected from 17 students through motor ability tests, including the Shuttle Run, throw and catch ball, and Stork Stand Positional Balance tests. Pre-test and post-test results were analyzed to obtain average scores, standard deviations, and variances. The research findings indicate an enhancement in students' motor skills following the implementation of small games in PESH learning. In the Shuttle Run test, there was an increase in the average score from the pre-test (19.2141) to the post-test (18.7294). The throw and catch ball test also exhibited an improvement in the average score from the pre-test (16.4118) to the post-test (19.6471). In the Stork Stand Positional Balance test, an increase in motor skills was also observed, with the average score shifting from the pre-test (11.3618) to the post-test (7.9676). Furthermore, statistical analysis also indicates a decrease in the standard deviations and variances in the post-test results compared to the pre-test, indicating an enhancement in measurement consistency. This improvement reaches approximately 13.73% in the enhancement of students' motor skills. The results of this research offer positive implications for the effectiveness of using small games to enhance students' motor skills within PESH learning. This underscores the significance of creative and playful approaches in optimizing the learning process to achieve holistic physical education objectives.